The Relationship Between TISE and TPACK among Prospective Biology Teachers of UNNES - Anggraeni, Nurlita; Ridlo, Saiful; Setiati, Ning (FMIPA UNNES, 2018)
The purposes of this study were to identify and describe level of TISE and TPACK as well as relationship between TISE and TPACK of prospective biology teacher 2014 and 2015 batches of UNNES. Quantitative descriptive was chosen as the design for this study. A total of 190 prospective biology teachers 2014 and 2015 batches participated in this study. The instruments used were the Computer Technology Integration Survey from Wang et al., TPACK survey from Pamuk et al. and interview guidelines. The results of this study were most of prospective biology teachers had confidence in integrating technology and knowledge to integrate knowledge of technology, pedagogy and content in teaching biology. Correlation test result showed that most of TISE level of prospective teachers were in line with their TPACK level with correlation coefficient r=0,611 and p<0.05. The conclusions of this study were most of prospective biology teachers had moderate level of TISE and TPACK also there was a significant positive relationship between the level of TISE with TPACK among prospective biology teachers.